El juez de ejecución de penas y las medidas de seguridad en Colombia: un análisis crítico sobre sus orígenes, consagración normativa y funciones (2020)
The purpose of this article is to critically examine the figure of the judge for the enforcement of penalties and security measures in Colombia from its origin, legal nature, duties, functions, and competence. This papers also recalls the laws and agreements of the Superior Council of Judicature that made possible the emergence and implementation of this specific category of official. The methodology for this examination is based on a documentary research developed through doctrinal and jurisprudential consultation, regulations, agreements, and reports of the National Penitentiary and Prisons Institute (Inpec) to collect data supporting the research for an approach analysis of the object of study so as to conclude on its effectiveness according to its functions. Among the findings, the importance of this official in the execution of guilty verdicts as the person in charge of ensuring compliance with convictions is pointed out. Nevertheless, according to the inspection function that this kind of constitutional judge has through the executing phase of the verdict, the role has become meaningless due to the persistent violation of the prisoner’s human rights, according to what the jurisprudence has stated.